Identification of developmentally-specific kinotypes and mechanisms of Varroa mite resistance through whole-organism, kinome analysis of honeybee - Robertson, Albert J.; Trost, Brett; Scruten, Erin; Robertson, Thomas; Mostajeran, Mohammad; Connor, Wayne; Kusalik, Anthony; Griebel, Philip; Napper, Scott (Frontiers in Genetics, 2014)
Recent investigations associate Varroa destructor (Mesostigmata: Varroidae) parasitism and its associated pathogens and agricultural pesticides with negative effects on colony health, resulting in sporadic global declines in domestic honeybee (Apis mellifera) populations. These events have motivated efforts to develop research tools that can offer insight into the causes of declining bee health as well as identify biomarkers to guide breeding programs. Here we report the development of a bee-specific peptide array for characterizing global cellular kinase activity in whole bee extracts. The arrays reveal distinct, developmentally-specific signaling profiles between bees with differential susceptibility to infestation by Varroa mites. Gene ontology analysis of the differentially phosphorylated peptides indicates that the differential susceptibility to Varroa mite infestation does not reflect compromised immunity; rather, there is evidence for mite-mediated immune suppression within the susceptible phenotype that may reduce the ability of these bees to counter secondary viral infections. This hypothesis is supported by the demonstration of more diverse viral infections in mite-infested, susceptible adult bees. The bee-specific peptide arrays are an effective tool for understanding the molecular basis of this complex phenotype as well as for the discovery and utilization of phosphorylation biomarkers for breeding programs.